Nilai Moral Tokoh Utama Film Our Times《我的少女时代》Karya Frankie Chen - Agustine, Leonita; Yusuf Arifin, Yohan (Jayapangus Press, 2024)
Movies nowadays not only serve as entertainment but also function as a means of communication to convey messages and life values to the audience. One film that has a special value, particularly moral value, is the movie Our Times《我的少女时代》. The purpose of this study is to determine the moral values of the main characters in the film Our Times《我的少女时代》. This research uses a qualitative descriptive approach. Every monologue and dialogue related to moral values are observed, noted, and recorded as the data collection method. After the data is collected, the author analyzes it using James Rachels' moral value theory, which includes courage, compassion, honesty, and loyalty. Based on the results and discussion, it can be concluded that the moral values in the film Our Times《我的少女时代》, using James Rachels' moral value theory, show alignment with the data found. The moral value of loyalty is the most dominant value in the film Our Times《我的少女时代》. The main characters, Lin Zhenxin and Xu Taiyu exhibit the most moral values.